Child welfare: the challenges of collaboration - Ross, Timothy (Urban Institute Press, 2009)
Cross-cutting issues in child welfare -- Coordinating law enforcement and child protection in cases of severe child maltreatment -- Does the criminal justice system force children into foster care? -- Hard data on hard times : an empirical analysis of maternal incarceration, foster care, and visitation -- A cohort analysis of adolescents in foster care -- Youth who chronically leave foster care without permission : why they run, where they go, and what can be done -- Betwixt and between : status offenders and foster care -- Bridging child welfare and juvenile justice : preventing the unnecessary detention of foster children / Timothy Ross and Dylan Conger -- An outcome evaluation of project confirm / Dylan Conger and Timothy Ross -- Solving cross-agency challenges